(untitled) (Experimental biology, 2024)
This article is dedicated to studying the influence of ash element distribution in the tissues of woody plants` foliar organs on the fluctuating asymmetry of leaf blades in industrial areas. The research objects are leaves of Populus balsamifera, Betula pendula, Acer negundo. The leaves were collected at the end of the 2023 growing season, with subsequent measurements of the length and width of the leaf blade and calculation of the standard deviation. The significance of differences between samples was assessed based on the results of variance analysis. Ash content determination was carried out by the dry ashing method of leaves in a muffle furnace. The obtained results confirm a direct proportional relationship between significant fluctuations in morphometric parameters as ash content increases, which can be used as an indicative method of anthropogenic pollution in industrial regions.